(3RHOI GdHjGf aj CMcGe GdbQBfs - (3GdCQOHjdj, CMeO Hf eMeO, J (B993 (3g`s ((3eOQSI GdLOI GdYdjI aj OGQ GdCUagGfs)
(3ChdgG (B:s
... (3aEfg CSgd PfH aEf GdQej HGdaGMTI CSgd efg aYdgG (B... (3hGdcGaQ EPG Qei haYd ZjQg CaYGd dGGdMQ (B.. (3JbHd JhHJg (B...s
(3BNQgG (B:s
... (3eY chf SHH GdfRhd NGUG XGgQ Je JbOjQ GdJNUjU (B.. (3dG jYjO GdJYeje dage Cgdg (B... (3GdHGbj aJCed (B. (3Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B1/234s
(3EjVGM Gdecfhf , ddHZOGOj (B3/609s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs